2010
DOI: 10.1159/000290656
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Negative p38 Mitogen-Activated Protein Kinase Expression Inhibits NF-κB Activation in AR42J Cells

Abstract: Background: The role of the p38 mitogen-activated protein (MAP) kinase in acute pancreatitis pathogenesis is controversial. We hypothesize that p38 plays a role in regulating NF-ĸB activation in exocrine pancreatic cells. Methods: AR42J cells incorporating an NF-ĸB-responsive luciferase reporter, with and without adenoviral transduction of DNp38, were stimulated with cholecystokinin (CCK) or tumor necrosis factor-α (TNF-α) prior to measuring NF-ĸB activation. Results: CCK- or TNF-α-stimulated NF-ĸB-dependent g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Thus, a pool of excess, unactivated p38δ-WT could perturb this regulatory system, or may simply compete with the population of endogenous activated p38, resulting in inhibition of L1. Consistent with this possibility are several studies that showed expression of a nonfunctional p38 has a dominant negative effect on endogenous p38 activity [4246]. In addition, during some of our own preliminary experiments, we found on rare occasion that exogenous p38δ-WT slightly increased rather than decreased the number of G418-resistant colonies (unpublished data), further suggesting that the effect of exogenous p38δ-WT could depend on cellular conditions that affect the p38 pathway.…”
Section: Resultssupporting
confidence: 87%
“…Thus, a pool of excess, unactivated p38δ-WT could perturb this regulatory system, or may simply compete with the population of endogenous activated p38, resulting in inhibition of L1. Consistent with this possibility are several studies that showed expression of a nonfunctional p38 has a dominant negative effect on endogenous p38 activity [4246]. In addition, during some of our own preliminary experiments, we found on rare occasion that exogenous p38δ-WT slightly increased rather than decreased the number of G418-resistant colonies (unpublished data), further suggesting that the effect of exogenous p38δ-WT could depend on cellular conditions that affect the p38 pathway.…”
Section: Resultssupporting
confidence: 87%
“…EMSA electrophoretic mobility shift assay, NF-κB nuclear factor κB, SO sham operation, SAP severe acute pancreatitis, Taur taurine. Studies showed that p38 MAPK plays an important role in the pathogenesis of SAP [3,30]. The expression of phosphorylated p38 MAPK in the pancreatic and lung tissue was increased rapidly in the SAP rat model [3].…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[20][21][22][23][24][25][26] We have previously shown that ERK, NF-κB, and AP-1 are activated in the mouse pancreas within 1 h of pancreatic duct ligation, 1 while here we have shown that pancreatic ERK activation is sustained and also progresses until the premortal state in acute pancreatitis; also, pulmonary ERK activation peaks on day 3. As we have observed that ERK inhibition reverses agoniststimulated increases in NF-κB-dependent gene transcription in an exocrine pancreatic malignant cell line (AR42J cells) 5 while p38 inhibition only partially reduces it, 6 we are currently focusing on the role of ERK in disease pathogenesis in ligation-induced acute pancreatitis in mice.…”
Section: Discussionmentioning
confidence: 99%